Identify Factors in Increasing the Income of Micro, Small and Medium Enterprises (MSMEs) in Padang City - Nadilla, Nia; Parwati, Tri Ayu; Diana, Yusvi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2024)
Micro, Small and Medium Enterprises (MSMEs) are the largest segment for national economic actors. MSME players can help the government reduce the number of unemployed people. So in Indonesia, micro, small and medium enterprises are often associated with government efforts to reduce unemployment, fight poverty, and equalize income. This research aims to identify the factors that influence the income of MSMEs in the city of Padang. The research design used in this research is causative research to identify factors that influence the income of micro, small and medium businesses in the city of Padang, where the research subjects used a purposive sampling approach with a margin of error of 5% so that the number of samples of micro and small business actors who have been and Having carried out digital promotions, the target was 385 respondents as measured by distributing a Likert scale questionnaire. Data analysis uses validity, reliability, classical assumption tests, multiple regression tests, F-tests and t-tests. The results of data analysis show that the role of government, capital, entrepreneurial competence and length of business have a significant effect, both partially and significantly, on MSME income.